Safety Risk Assessment on Aircraft Marshaling Case Study at Indonesian Civil Pilot Academy of Banyuwangi - Wicaksono, Agung Wahyu; Patompo, Putri Annatasah; Globalisasi, Safitri Era (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
Aviation is subject to risks that emerge from all activities correlated with flight operations. Indonesian Aviation Academy Banyuwangi as an educational institution that participating in such activities, it is susceptible to various risks, ranging from the minor to the major risks. The marshaling activity is one of the crucial flight activities conducted by cadets of the Indonesian Civil Pilot Academy of Banyuwangi. This activity can be hazardous if not conducted properly and in compliance with the procedures. This research aims to determine the risks of marshaling activities at the Indonesian Civil Pilot Academy of Banyuwangi and propose effective mitigation strategies. The qualitative methodology was chosen in this research utilizing three stages of data collection techniques: observation, literature study, and interviews. The research results show that three primary risks occur in marshaling activities at the Indonesian Civil Pilot Academy of Banyuwangi, in particular, not using earplugs, not using safety vests and unclear parking markings. These three risks attributed to a lack of accountability, the absence of standard operating procedures, and insufficient provision of necessary equipment by the organization.